2005
DOI: 10.1258/000456305774538210
|View full text |Cite
|
Sign up to set email alerts
|

Detection assessment and monitoring of hepatic fibrosis: biochemistry or biopsy?

Abstract: Hepatic fibrosis is an important consequence of inflammatory disorders affecting the liver, and ultimately progresses to cirrhosis. Here we explore methods for the detection and monitoring of hepatic fibrosis, particularly in hepatitis C, alcoholic liver disease, non-alcoholic fatty liver disease and during methotrexate therapy, in all of which progressive fibrosis can develop over a number of years in a minority of patients. Liver biopsy currently remains the gold standard to assess fibrosis. However, it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 66 publications
(64 reference statements)
0
22
0
3
Order By: Relevance
“…This parotid damage could be enlightened by another mechanism where MTX binds to dihydrofolic reductase preventing the change of folic to folinic acid (its active form). This, in turn, hinders nucleic acids, amino acids and proteins synthesis with consequent membrane damage, cellular death and altered salivary secretion [41] . Such mechanism was supported by the marked reduction obtained in acinar and ID secretory granules size and content, significant decrease in total protein, amylase activity and acini and ducts' numbers.…”
Section: Discussionmentioning
confidence: 99%
“…This parotid damage could be enlightened by another mechanism where MTX binds to dihydrofolic reductase preventing the change of folic to folinic acid (its active form). This, in turn, hinders nucleic acids, amino acids and proteins synthesis with consequent membrane damage, cellular death and altered salivary secretion [41] . Such mechanism was supported by the marked reduction obtained in acinar and ID secretory granules size and content, significant decrease in total protein, amylase activity and acini and ducts' numbers.…”
Section: Discussionmentioning
confidence: 99%
“…However, these noninvasive tests are cumbersome, expensive, and do not fulfill the criteria of an ideal test for hepatic fibrosis. [17][18][19][26][27][28] Liver biopsy and most noninvasive tests are not feasible for communitybased screening; and another simple, inexpensive, accurate, and easily applicable parameter is necessary. The platelet count is a simple test, and its results are determined easily by routine laboratory procedure.…”
Section: Discussionmentioning
confidence: 99%
“…We need to be specific about what we are trying to detect in an LFT screening test. It has long been recognised that ALT elevation is poorly correlated with the severity of histologic liver disease in chronic liver disease [24,25]. Mofrad et al [26] reported on a cohort of patients with normal ALT levels who were diagnosed as having NAFLD histologically and identified clinically (persistent hepatomegaly) or because the subjects were live liver transplant donors.…”
Section: Specificity and Sensitivity Of The Lftmentioning
confidence: 99%